Investigating the Effect of Academicians’ Cyberloafing Behaviors on Job Stress by Generation - Mahmut Demirkıran; Emel Esen (İstanbul İktisat Dergisi)
This study aims to examine the effect of academicians’ cyberloafing behaviors on work stress by generation and whether cyberloafing and job stress levels differ with respect to demographic variables and the antecedents of cyberloafing. The study accessed 383 academicians in Türkiye using the convenience sampling method and obtained data using the survey method. The study applied a correlation analysis, the Kruskal-Wallis H test, and the Mann-Whitney U test to the obtained data and consequently determined no significant relationship to be present between job stress and cyberloafing. The academicians were seen to exhibit more minor cyberloafing behaviors and to have below-average cyberloafing and job stress levels. The Generation-Y (Millennial) academicians were found to have higher cyberloafing and job stress levels compared to the Generation-X academicians. The study’s use of an academician sample and examination of the generational relationship between cyberloafing and work stress reveals the study’s importance and difference from other studies in the literature.